Binocular Vision and Accommodative Testing in the TeleOptometric Comprehensive Eye Examination in a Student Population. - Randhawa, Harneet K.; McLeod, Heather M.; Kattouf, Valerie M.; Yi Pang; Sanghera, Navjit K. (Optometry & Visual Performance, 2023)
Background: Current research in the realm of teleoptometric examinations is largely focused on the refractive and ocular health components of the exam. The purpose of this study was to evaluate the validity of binocular vision and accommodative testing in a tele-optometric examination compared to an in-person examination. Methods: Thirty students, ≥18 years old, at the Illinois College of Optometry were recruited to participate in this study. A teleoptometric examination was completed using the DigitalOptometrics platform, followed by a standard in-person examination. The following tests were performed in both examinations: near horizontal heterophoria by von Graefe, near negative and positive fusional vergences (NFV and PFV, respectively) by Risley prism, and accommodative testing with fused cross-cylinder (FCC). Results: The mean near horizontal heterophoria by von Graefe was 2.09Δ ± 6.73∆ exophoria in the tele-optometric examinations and 2.07Δ ± 6.54∆ exophoria in the in-person examinations, with no statistically significant difference between the two examinations (p=0.98). The mean NFV break and recovery in the tele-optometric examination were 10.85∆ ± 3.17∆ and 7.08∆ ± 3.03∆, respectively, and 23.40∆ ± 7.71∆ and 15.38∆ ±7.31∆, respectively, in the in-person examination, with a statistically significant difference (for both, p<0.0001). The mean PFV break and recovery in the tele-optometric examination were 13.50Δ ± 4.24Δ and 9.36Δ ± 4.68Δ, respectively, and 25.86Δ ± 10.48Δ and 16.54Δ ± 7.18Δ, respectively, in the inperson examination, with a statistically significant difference (break: p=0.001, recovery: p=0.004). Agreement of NFV and PFV between the two examinations was poor. The average FCC in the tele-optometric versus in-person examination was +0.67 D ± 0.51 D and +0.96 D ± 0.33 D, respectively, with a statistically significant difference between the two examinations (p=0.012). Conclusions: The tele-optometric and inperson examinations had fair agreement on near heterophoria but poor agreement on break and recovery values of NFV and PFV. Accommodative testing with FCC was not equivalent between the two exams.